Communication and human rights - Sen, A. Fulya (Elsevier Science Bv, 2015)
Communication represents an essential and very important human need as well as a basic human right. The right to communication should be considered in the framework of the freedom of expression and the pluralist democracy. The recognition of the right to communicate is essential to the overall defence of human rights standards. The general right of communication provides to exchange opinions, thoughts and meanings. In this study, it will be dealt with the importance of the right to communicate in human rights concept. The concept of the right to communicate will be discussed in terms of the freedom of expression, pluralist media and the freedom of internet in a democratic society. (C) 2015 The authors Published by Elsevier Ltd.
5th International Conference on New Horizons in Education (INTE) -- JUN 25-27, 2014 -- Paris, FRANCE
Keywords: Human rights; the right to communicate; pluralist media; democracy